The age of Jackson and the art of American power, 1815-1848 - Nester, William R., 1956- (Potomac Books, 2013)
As William Nester asserts in The Age of Jackson, it takes quite a leader to personify an age. A political titan for thirty-three years (1815-1848), Andrew Jackson possessed character, beliefs, and acts that dominated American politics. Although Jackson returned to his Tennessee plantation in March 1837 after serving eight years as president, he continued to overshadow American politics. Two of his proteges, Martin ""the Magician"" van Buren and James ""Young Hickory"" Polk, followed him to the White House and pursued his agenda. Jackson provoked firestorms of political passions throughout his